The Development of the Egyptian Technical Secondary Education Considering Some Contemporary Global Trends: An Analytical Study - Mahmoud, Khaled Salah Hanafy (European Journal of Social Science Education and Research, 2021)
Technical education is the base for all development efforts in society. It plays an important role in pushing up the development wheel and in achieving its maximum rates. Whatever the development plans quality, they couldn’t achieve their goals and targeted rates without the availability of scientifically and technically qualified human cadre in all work and production fields. Studies clarified that Egyptian technical secondary education suffers from many problems as the weak of its programs leading to negative effects on the proficiency of their students and their outcomes, their inconvenience to the labor market and making gap between the educational outcomes and technical education institutions and leading to the inferiority of the social status of this sort of education considering its relationship with hand work. Thus, reinforcement of the positive social sight towards vocational and technical education in Egypt represents a challenge. This study attempted through using the analytical method, through analyzing the educational literature to identify the contemporary global trends in developing technical education, how to apply every trend in the other world countries and to identify the positive and negative sides of applying every trend. Thus, the development of Egyptian technical secondary education could be identified and its requirements and means.